Pengembangan Multimedia Pembelajaran Interaktif Pada Mata Pelajaran Pengolahan Citra Digital di Sekolah Menengah Kejuruan Negeri 8 Semarang - Yuli Sintya Maharani; Nunuk Suryani; Deny Tri Ardianto (Teknodika, 2018)
This research aims to; (1) describe the needs of subjects Digital Image Processing class XI Multimedia at SMK N 8 Semarang, (2) development of Interactive Digital Image Processing class XI Multimedia at SMK N 8 Semarang, and (3) Measurement of multimedia effectiveness Product development on image processing subjects Digital class XI Multimedia at SMK N 8 Semarang. This research was research and development, which referred to the ADDIE model. The Learning interctive multimedia was developed through five stages, the developmental steps begun by analyzing the requirements, design, manufacturing, implementation,and evaluation. The process assesses the feasibility of learning media by providing questionnaires to media experts, material experts, and test respondents (students). Data questionnaire is then processed to determine the feasibility of media. The results of this study is interactive multimedia learning products with Adobe Flash application base. This can be seen from the validation of material experts with an average of 4.51 and has a very good category. Validation of media experts with an average of 4.59 is a very good category. According to the students, this multimedia is very good with an average of 4.61.  The result of this research showed that the developed media had been fulfilled the requisites and worthy of being a medium of learning. The result of t-test by using paired sample t-test obtained result that on α = 5 % with DK ={t|t ≤ −t0.025;33 = −2,03 or t ≥ t0.025;33 = 2,03} and tobs = -7,29, maka –tobs = −7.297 ≥ −ttable = −2.034. And was obtained value Sig. (2-tailed)= 0.000 <0.05, therefore, it can be concluded that both groups have unequal achievement. The experimental class has an average of 85.41 while the control class has an average of 71.29. So it can be concluded learning multimedia is effective to be used in the learning activity and can improve student achievement.